Physical activity and eating habits of students of the University of Belgrade: An epidemiological study - Obradović, Miloš; Nešić, Goran; Popović, Aleksandra; Božić, Predrag; Savić, Zoran; Kojić, Filip; Djuric, Saša (Vojnosanitetski pregled, 2022)
Background/Aim Numerous studies have indicated that university students exhibit a variety of risky health behaviors, such as the lack of regular physical activity and unhealthy eating habits. Due to lack of information about students’ lifestyle in Serbia, we have designed a study with aims: (1) to investigate physical activity and eating habits variations by gender, year of study and attended faculty; and (2) relationship between physical activity and eating habits. Methods The Survey research method was used. Data were collected in school year 2016/2017 during spring semester. Sample was randomly stratified (4019 students of the University of Belgrade – 2284 males), that corresponded about 5% of the whole student population of the University of Belgrade. For data collection, two standardized questionnaires were used: International Physical Activity Questionnaire (IPAQ) and Youth/Adolescent Food Questionnaire (YAQ). Results Male students were significantly more vigorously and moderately active than female students (3.15 vs 2.80 days, respectively; p = 0.003, ES = 0.651). Correspondingly, female students were sedentary inactive during the day (326 vs 305 min; p = 0.044, ES = 0.232). The interaction between factors revealed that the most vigorously active on weakly basis were fourth year male students of natural-mathematical sciences (4.20 days), while on daily basis were first year female students (161 min). The most sedentary ones were third year female students of medical sciences (475 min of sitting per day). Significant correlations were found between the time being vigorously active and consuming water, vegetables, citrus fruits, integral bread, and cereals. Conclusion Female students were more likely declined to sedentary behavior, older students were more active and aware of importance of physical activity, while nature of studies can influence the lifestyle. Female and older students were more concerned about diets. Additionally, students who were more physically active had healthier eating habits.